Protected Areas Are Important for the Conservation of Disa engleriana, an Edible Orchid in Malawi - Blessings Tionge Chingagwe; Gift Gladson Moyo; Elizabeth Mwafongo; Tiwonge I. Mzumara; Jean Cossi Ganglo (Ecology and Evolution)
ABSTRACT Edible orchids are increasingly threatened by unsustainable use in their natural habitats. Several studies highlight the need for propagation to counter this threat. However, a critical gap persists in understanding the environmental conditions that support these species in Malawi. This study aimed to identify potential habitats suitable for propagating edible orchids, focusing on Disa engleriana Kraenzl, 1893, to enhance ex situ conservation efforts. Present and future environmental data were sourced from WorldClim. Species occurrence data were obtained during field surveys and existing datasets. Using MaxEnt, continuous habitat suitability for D. engleriana was modeled based on presence‐only occurrence data, Bioclim variables, and elevation. The integration of ArcGIS allowed for a detailed analysis, reclassifying the continuous suitability map into suitable and unsuitable habitats. The results of the study show that most suitable habitats align with the boundaries of protected areas, emphasizing their critical importance in conservation planning. The study further found that suitable habitats for D. engleriana are typically at altitudes between 1500 and 1600 m, with temperatures not exceeding 15°C during the wettest months. In addition to that, the results revealed the negative impact of climate change on habitat suitability, projecting a decrease in suitable areas over the next 50 years.